Fast and quantitative mitophagy assessment by flow cytometry using the mito-QC reporter - Jiménez-Loygorri, Juan Ignacio; Jiménez-García, Carlos; Viedma-Poyatos, Álvaro; Boya, Patricia (Frontiers in Cell and Developmental Biology, 2024)
Mitochondrial quality control is finely tuned by mitophagy, the selective degradation of mitochondria through autophagy, and mitochondrial biogenesis. Removal of damaged mitochondria is essential to preserve cellular bioenergetics and prevent detrimental events such as sustained mitoROS production, pro-apoptotic cytochrome c release or mtDNA leakage. The array of tools available to study mitophagy is very limited but in constant development. Almost a decade ago, we developed a method to assess mitophagy flux using MitoTracker Deep Red in combination with lysosomal inhibitors. Now, using the novel tandem-fluorescence reporter mito-QC (mCherry-GFP-FIS1101−152) that allows to differentiate between healthy mitochondria (mCherry+GFP+) and mitolysosomes (mCherry+GFP−), we have developed a robust and quantitative method to assess mitophagy by flow cytometry. This approach has been validated in ARPE-19 cells using PINK1/Parkin-dependent (CCCP) and PINK1/Parkin-independent (DFP) positive controls and complementary techniques. Furthermore, we show that the mito-QC reporter can be multiplexed, especially if using spectral flow cytometry, to simultaneously study other cellular parameters such as viability or ROS production. Using this technique, we evaluated and characterized two prospective mitophagy inducers and further dissected their mechanism of action. Finally, using mito-QC reporter mice, we developed a protocol to measure mitophagy levels in the retina ex vivo. This novel methodology will propel mitophagy research forward and accelerate the discovery of novel mitophagy modulators.